Effectiveness of Archive Arrangement at Pelindo Multi Terminal Branch Makassar Sub Holding Office (Pinisi Journal of Officers Review, 2024)
Organize archives neatly and organized so that they are easily found and used by people who need them. This study aims to determine how effective the arrangement of archives at the Makassar Sub holding Office of Pelindo Multi Terminal Branch. Therefore, research has significant in identifying archival structuring that affects effectiveness in archival. This research is qualitative, therefore, to achieve the objectives of the study, data collection techniques are used, namely observation, interviews, and documentation. The results of this study show that all indicators used in this study are classified as less effective. The indicator in question is that archive storage is classified as effective because archives are stored or placed in file cabinets, archives are also stored based on numbers or dates then store them in archive boxes, archive placement is classified as less effective because the items in the box are not arranged properly and the rediscovery of archives is classified as less effective because it takes a while to find the items you are looking for in many collections of old items. This study presents new information by relating detailed theories and research loci different from previous research on the effectiveness of archival structuring so that it can be used as evaluation material for research loci to increase effectiveness in archives